PENGEMBANGAN E-MODULE KIMIA BERBASIS POGIL (PROCESS ORIENTED GUIDED INQUIRY LEARNING) PADA MATERI REAKSI REDUKSI-OKSIDASI SEBAGAI SUMBER BELAJAR SISWA - Retno Dwi Cahayningrum; Muktiningsih Nurjayadi; Arif Rahman (LPPM Universitas Negeri Jakarta, 2017)
This study aims to produce chemical-based e-Module POGIL (Process Oriented Guided Inquiry Learning) on the material oxidation-reduction reaction as a viable source of student learning. This research method using research and development or research and development (R & D). Subjects in this study were students of SMK class X. Data analysis techniques using an assessment analysis of 10 validators consisting of 5 material and language experts, as well as 5 media experts. Analysis of expert validation test questionnaires, Student and teacher trials using questionnaires that were adopted from Puskurbuk and issued by BSNP. Applications used in the manufacture of e-Module is 3D PageFlip Professional 1.7.7. The results of the study show that: (1) Assessment of experts as a whole is obtained in the range of 70% to 90% with good to excellent interpretation, (2) Assessment of teachers and students on a small scale and large scale as a whole increases in the range 80% 90% with good to good interpretation. Thus, it can be concluded that the e-Module POGIL material based chemical oxidation-reduction reactions are very well developed and already eligible for use in the learning process and can be used as a source of independent study students. Keywords: e-Module, POGIL, oxidation-reduction reaction, learning resources, 3D PageFlip